2010
DOI: 10.1091/mbc.e10-03-0212
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pzg-NURF Complex Regulates Notch Target Gene Activity

Abstract: The Putzig (Pzg) protein is associated with the NURF nucleosome remodeling complex, thereby promoting Notch target gene expression. Our findings suggest a novel Pzg-NURF complex that is responsible for the epigenetic regulation of Notch target genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…Specifically, in 1 mammalian cells, the histone acetyl transferases (HATs) PCAF (KAT2B) and GCN5 (KAT2A) have been shown biochemically to function in RBPJ [the mammalian homolog of Su(H)]-mediated transactivation by N ICD (Kurooka and Honjo, 2000). In flies, the RING-finger E3 ubiquitin ligase Bre1 and chromatin remodeling complex NURF have been shown to be involved in the epigenetic regulation of Notch target gene expression (Bray et al, 2005;Kugler and Nagel, 2010). Recently, an RNAi screen in cultured Drosophila cells revealed that a Notch pathway transcriptional reporter is sensitive to chromatin-modifying enzymes and remodelers (Mourikis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in 1 mammalian cells, the histone acetyl transferases (HATs) PCAF (KAT2B) and GCN5 (KAT2A) have been shown biochemically to function in RBPJ [the mammalian homolog of Su(H)]-mediated transactivation by N ICD (Kurooka and Honjo, 2000). In flies, the RING-finger E3 ubiquitin ligase Bre1 and chromatin remodeling complex NURF have been shown to be involved in the epigenetic regulation of Notch target gene expression (Bray et al, 2005;Kugler and Nagel, 2010). Recently, an RNAi screen in cultured Drosophila cells revealed that a Notch pathway transcriptional reporter is sensitive to chromatin-modifying enzymes and remodelers (Mourikis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…At least three GAF-associated proteins with C2H2-type zinc finger motifs were confirmed to be GAF direct partners: CG2199, Pzg/Z4, and MEP-1 [163]. MEP-1 and Pzg/Z4 are known to be associated with chromatin remodeling activity [178,179]. Although GAF is a multifunctional factor implicated in different nuclear functions, these proteins can be implicated in the PcG/TrxG system as well.…”
Section: Much More Dna-binding Proteins Waits To Be Identifiedmentioning
confidence: 99%
“…Many studies show interactions between components of the NURF complex, or the highly related FAC1 protein (Fetal Alz-50-reactive Clone 1), and sequence specific transcription factors (Table 1) [9,[53][54][55][56][57][58][59][60][61][62][63][64][65]. FAC1 has sequence identity to the N-terminus of the human NURF301 homolog BPTF, strongly suggesting the two are related [66,67].…”
Section: Nurf and Its Interaction With Chromatinmentioning
confidence: 99%